Novel Biomarkers in the Continuum of Breast Cancer - Stearns, Vered (Breast Cancer Research Foundation, 2016)
This volume provides a comprehensive review of established and novel biomarkers across the continuum of breast cancer. The volume covers topics related to breast cancer risk and prevention, prediction of response to today's standard therapies, and markers capable of influencing treatment decisions in the near future. Chapter authors combine their wide-ranging expertise to review the current status of the biomarker and to offer their individual perspectives on how biomarkers may be used in future treatments and research. Breast cancer continues to be the most common malignancy diagnosed in women in the Western world. While there are multiple treatment approaches for breast cancer, today more than ever we recognize that each tumor is unique. The challenge ahead is to consider how to best use validated and novel biomarkers to select the most appropriate treatment for individual patients.